Anti-acetylcholine receptor antibody titres in the sera of myasthenia patients treated with plasma exchange combined with immunosuppressive therapy. Issue 5 (May 1980) - Carter, B; Harrison, R; Lunt, G G; Behan, P O; Simpson, J A
Abstract : Anti-acetylcholine receptor antibody titres have been monitored in the sera of 19 myasthenic patients treated with plasma exchange combined with a three month period of immunosuppressive therapy. In general the post-exchange titres stabilised at below pre-exchange levels for prolonged periods which were associated with clinical improvement. In seven instances recurrence of symptoms occurred and in six of these cases relapse was shown to be associated with a rise in anti-acetylcholine receptor antibody titre.